EDUCATIONAL TECHNOLOGIES AS A METHOD (ResearchJet Journal of Analysis and Inventions, 2022)
The article examines the use of modern educational technologies as a method and their effectiveness, the development of the student's mind, their positive and negative consequences in the use of educational technologies, and ways of organizing distance education.